Comprehensive review of generalized anxiety disorder in primary care in Europe. (April 2013) - Parmentier, H.; García-Campayo, J.; Prieto, R.
Abstract Objective: This review aims to summarize meta-analyses and other relevant data relating to the efficacy and safety of the various treatment options for generalized anxiety disorder (GAD) in Europe. In addition, it will provide an overview of the prevalence, burden, and recognition of the disorder, with a view to raise awareness of GAD and inform primary care practitioners. Research design and methods: Relevant research or review articles on psychological or pharmacological treatments for GAD published in the English language between March 2006 and March 2012 were identified via a literature search in PubMed and ISI Web of Knowledge and from the Cochrane Library. Other relevant references/clinical guidelines were individually selected by the authors. Results: Prevalence rates of GAD vary across Europe but its economic and social burden is increasing. A large proportion of patients with GAD present with symptoms in primary care. However, due to the disorder's complexity and the incidence of comorbid diseases, some primary care physicians may lack the knowledge or confidence to effectively recognize, manage, and/or treat the disorder. This is despite psychological and pharmacological treatments being available for the effective management of GAD. Conclusions: GAD remains a difficult disorder to detect and comorbid complications add to its economic and social burden. Early detection and intervention reduces the societal burden and improves GAD patients' quality of life and functional ability. Primary care practitioners play a key role in identifying and treating patients with GAD.